"We'd get slagged and bullied": understanding barriers to volunteering among young people in deprived urban areas. (17th December 2018) - Davies, James
Abstract : This article explores barriers to formal volunteering opportunities among young people, aged 12–18, in deprived urban areas in Glasgow, Scotland. It draws on qualitative fieldwork conducted with young volunteers, non-volunteers and youth workers. The article employs Bourdieu's concept of 'habitus' to analyse how objective conditions and subjective dispositions created obstacles to participation. Findings indicate that participants were constrained from accessing volunteering due to: resource issues in youth organisations; a lack of support from schools; a lack of information; and restrictions on their spatial mobilities. These constraints provided conditions in which volunteering became subject to informal penalties. These were not, however, experienced in a uniform manner but intersected with gender and individual trajectories to create varying opportunities for volunteering.